2009
DOI: 10.1210/jc.2008-1440
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Effects of Levothyroxine in Iron-Deficient Subclinical Hypothyroid Patients: A Randomized, Double-Blind, Controlled Study

Abstract: Subclinical hypothyroidism should be treated in iron-deficiency anemia patients when both conditions coexist. This would provide a desired therapeutic response to oral iron replacement and prevent ineffective iron therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 23 publications
4
71
1
5
Order By: Relevance
“…In a study carried out by Cinemre H. and colleagues, they showed that the efficacy and absorption of oral iron treatment in women with subclinical hypothyroidism improved after levothyroxine replacement. This demonstrates that hypothyroidism should be assessed in patients with anemia [8].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a study carried out by Cinemre H. and colleagues, they showed that the efficacy and absorption of oral iron treatment in women with subclinical hypothyroidism improved after levothyroxine replacement. This demonstrates that hypothyroidism should be assessed in patients with anemia [8].…”
Section: Discussionmentioning
confidence: 84%
“…Iron deficiency anemia is related with menorrhagia occurring as a result of various hormonal imbalances and also malabsorption which is seen in hypothyroidism [7,8]. Folic acid is another vitamin with impaired intestinal absorption, and causing macrocytic anemia in hypothyroidism [9].…”
mentioning
confidence: 99%
“…[14,[20][21][22] To the best of our knowledge, this is the first study to report the prevalence of thyroiditis-induced anemia in non-pregnant females during the childbearing age in Saudi Arabia. The present study showed thyroid abnormalities in 19.6% of the study population and the most common thyroid disorders were subclinical hypothyroidism followed by overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…[21,22] Anemia of chronic disease, which is in the form of normocytic normochromic anemia, is the most frequently encountered type of anemia in hypothyroidism. [8,16] It has been suggested that thyroid hormone deficiency may lead to bone marrow repression and/or decrease in erythropoietin production due to the reduction of O 2 requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation